2016
DOI: 10.1186/s12887-016-0712-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum phosphate and magnesium in children recovering from severe acute undernutrition in Ethiopia: an observational study

Abstract: BackgroundChildren with severe acute malnutrition (SAM) have increased requirements for phosphorus and magnesium during recovery. If requirements are not met, the children may develop refeeding hypophosphatemia and hypomagnesemia. However, little is known about the effect of current therapeutic diets (F-75 and F-100) on serum phosphate (S-phosphate) and magnesium (S-magnesium) in children with SAM.MethodsProspective observational study, with measurements of S-phosphate and S-magnesium at admission, prior to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
(22 reference statements)
4
4
0
Order By: Relevance
“…Hypophosphatemia was present in 20% (n=25) of the 126 children in the current study (Table 3), which concurs with other studies that have reported low phosphate levels on hospital admission for children with SAM [9,18]. In agreement with the findings of Mbethe and Mda [4], hypophosphatemia was significantly (p=0.04) associated with RFS in the current study [5].…”
Section: Discussionsupporting
confidence: 92%
“…Hypophosphatemia was present in 20% (n=25) of the 126 children in the current study (Table 3), which concurs with other studies that have reported low phosphate levels on hospital admission for children with SAM [9,18]. In agreement with the findings of Mbethe and Mda [4], hypophosphatemia was significantly (p=0.04) associated with RFS in the current study [5].…”
Section: Discussionsupporting
confidence: 92%
“…There was no significant difference in phosphate levels of children with or without diarrhea and dehydration. This was in accordance with studies done by Kimutai et al [3], Hother et al [4] and Okinyi et al [9]. However, Namusoke et al [5] reported a significant difference in hypophosphatemia prevalence at transition in children with or without diarrhea.…”
Section: Discussionsupporting
confidence: 91%
“…Prevalence of hypophosphatemia in our study was 25%, 23.3% and 8.3% on admission, during transition and at discharge, respectively. The prevalence on admission was comparable with studies by Namusoke et al (37%) and Dakshayani et al (17%) [5,8], while Kimutai et al (86%), Hother et al (93%) and Chanchal et al (60%) reported very high prevalence [3,4,7]. Higher prevalence in the study by Kimutai et al could be explained by difference in study population as they enrolled only children with edematous malnutrition.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Other studies have reported a decrease in serum P on day 2 of treatment ( 21 , 22 , 27 , 28 ) . However, other studies ( 26 , 30 ) found increasing concentrations of serum P throughout the treatment period. This difference may be attributed to the type of therapeutic food used.…”
Section: Discussionmentioning
confidence: 73%